2013
DOI: 10.1371/journal.pone.0076692
|View full text |Cite
|
Sign up to set email alerts
|

A Humanized Monoclonal Antibody Specific for Invariant Natural Killer T (iNKT) Cells for In Vivo Depletion

Abstract: Invariant Natural Killer T (iNKT) cells are a subset of T cells recognizing glycolipid antigens presented by CD1d. Human iNKT cells express a conserved T cell receptor (TCR)-α chain (Vα24-Jα18) paired with a specific beta chain, Vβ11. The cells are both innate-like, with rapid cytokine release, and adaptive-like, including thymic positive selection. Over activation of iNKT cells can mediate tissue injury and inflammation in multiple organ systems and play a role in mediating the pathology associated with clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 19 publications
(20 reference statements)
3
30
0
Order By: Relevance
“…We have also demonstrated that the elimination of iNKT cells using NKT-14 was effective, and that it did not affect the total number of leukocytes in lung tissue, supporting the notion that NKT-14 is specific for iNKT cells [35, 44]. In this study, we show that targeting iNKT cells with NKT-14 also translated to an elimination of αGalCer induced AHR, further illustrating the specificity and impact of NKT-14.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We have also demonstrated that the elimination of iNKT cells using NKT-14 was effective, and that it did not affect the total number of leukocytes in lung tissue, supporting the notion that NKT-14 is specific for iNKT cells [35, 44]. In this study, we show that targeting iNKT cells with NKT-14 also translated to an elimination of αGalCer induced AHR, further illustrating the specificity and impact of NKT-14.…”
Section: Discussionsupporting
confidence: 78%
“…Bedel et al showed that the genetic modifications in the B6.Jα18 −/− mice were not limited to the iNKT cells but had widespread consequences on the T cell population in general. In this context, it is important to note that NKT-14 is specific for iNKT cells but does not affect the type II NKT cells [44]. The possibility to use a specific agent like NKT-14 therapeutically to deplete a cell type in a model is significantly different from studying a model in which the cell type never existed due to a gene knockout.…”
Section: Discussionmentioning
confidence: 99%
“…A humanized iNKT cell depleting antibody, NKTT120, targets the invariant T cell receptor and has recently been developed for application in iNKT-mediated inflammatory conditions such as asthma and sickle cell disease [17]. This antibody has been tested in a Phase I clinical trial (NCT01783691), and early reports show that at the highest tested dose (0.3mg/kg), no dose limiting toxicities are seen and iNKT cells are depleted for a minimum of 28 days before recovery [18].…”
Section: Invariant Natural Killer T Cell (Inkt) Targeted Therapiesmentioning
confidence: 99%
“…Preclinical studies showed depletion of iNKT cells and no effect on other natural killer cells. The T cell antibody response was not impaired in reponse to a KLH challenge [66]. A phase I trial planned to enroll 21 patients with SCD is currently recruiting (NCT 01783691).…”
Section: Targeting Inflammationmentioning
confidence: 99%